Advances and trends of modern and contemporary research on the geology of coal-measure minerals in China - Yong QIN (Meitian dizhi yu kantan)
BackgroundCoal-measure minerals (CMMs) play a significant role in ensuring the safe supply of mineral resources in China. Reviewing the advances and trends of research on the geology of CMMs in China holds great historical significance and practical value while potentially providing some insights into subsequent research. Advances Based on textual research and the analysis of logical relations, this study generalized the advances in research on the geology of CMMs in China into four aspects. (1) Increasingly improved geological theory system of CMMs: China’s classic theoretical system of coal field geology was formed in the second half of the 20th century, and the geological theory system focusing on coals, coal-measure gas, and coal-measure critical metals has been gradually developed since the 21st century. (2) Research on the origin and genesis of coals, advancing the international coal geology: The advancements include the development of the new coal metamorphism theory, the discovery of the world's youngest soft lignite, the reveal of late-stage coalification jumps, the establishment of the ordinary organic petrology, and the comprehensive ascertainment of the formation and evolutionary mechanisms of coals. (3) The unique CMM accumulation, distribution, and metallogenic theory: The specific outcomes include the establishment of multiple sedimentary and structural coal-controlling patterns, the reveal of the fundamental framework of coal accumulation in sea areas, the identification of deposits of various coal-measure critical metals, and the determination of the division schemes for coal-controlling geotectonic units and the metallogenic zones of coal-measure critical metals, and the development of a geological theory system for coalbed methane. (4) Significant achievements in the geological surveys and assessment of special coal resources: Specifically, the methodological system for the geological prediction and assessment of special coal types and high-quality, eco-friendly, and clean coal resources has been developed, the methodological system for the resource potential assessment of tar-rich coals and underground coal gasification has been formed, and the coal resources for related purposes have been preliminarily investigated. Prospects The analytical results indicate that major national demands determine the trends of research on the geology of CMMs. It is recommended to focus on four aspects in future geological study: the precise exploration and exploitation of coal resources, the exploration and orderly production of coal-measure gas, the exploration and exploitation of critical metals, and the geological guarantee for in situ fluidized coal mining. Additionally, it is necessary to pay attention to the accumulation mechanisms and resource prediction methods for helium in coal measures.